Mobilizing against Inequality: Unions, Immigrant Workers, and the Crisis of Capitalism - Lee H. Adler, Maite Tapia, and Lowell Turner (Cornell University Press, ILR Press, 2014)
The case studies collected in Mobilizing against Inequality expertly explore what is increasingly apparent to scholars, labor activists, and workers: traditional models of worker representation that have allowed workers to win a greater share of productivity and a political voice are failing to adapt to a changing economic and political environment. In recent decades, corporate-funded politicians have pushed trade liberalization, privatization, and austerity. Employers have shifted traditional employment relationships and informalized workers through â€œsubcontracting, privatization, or some other form of intermediary contracting arrangement in order to reduce labor costs and avoid regulations associated with formal employment.â€ 1 Workersâ€™ share of national income is in decline worldwide, in tandem with union density. Only 7 percent of the worldâ€™s formal economy is organized into free and independent trade unions. With a sharp decline in union density and collective bargaining coverage, inequality has increased dramatically and threatens global growth and stability. In the Global North, perhaps nowhere are these trends more clearly illustrated than in the expansion of low-wage workplaces, many of which employ a majority immigrant workforce. With globalization, many workers have seen their local economies devastated and been forced to seek employment in richer economies. International migration has become a large and growing phenomenon, with more than 200 million people now living outside of their home countries for extended periods. 2 Few poor migrants from rural areas can secure formal jobs or a path to citizenship. They rely instead on low wages from temporary, contingent,and informal employment to survive. Often this is in unseen and underappreciated jobs in agricultural, domestic work, the service sector, subcontracted maintenance services, or atomized supply chains.